Computer-Based or Human Patient Simulation-Based Case Analysis: Which Works Better for Teaching Diagnostic Reasoning Skills? - Wilson, Rebecca D.; Klein, James D.; Hagler, Debra (Nursing Education Perspectives (National League for Nursing), 2014)
AIM The purpose of this study was to determine whether a difference exists in learner performance and the type and frequency of diagnostic reasoning skills used, based on the method of case presentation. BACKGROUND Faculty can select from a variety of methods for presenting cases when teaching diagnostic reasoning, but little evidence exists with regard to how students use these skills while interacting with the cases. METHOD A total of 54 nursing students participated in two case analyses using human patient and computer-based simulations. Participant performance and diagnostic reasoning skills were analyzed. RESULTS Performance was significantly better with the human patient simulation case. All diagnostic reasoning skills were used during both methods of case presentation, with greater performance variation in the computer-based simulation. CONCLUSION Both human patient and computer-based simulations are beneficial for practicing diagnostic reasoning skills; however, these findings support the use of human patient simulations for improving student performance in case synthesis.